Impact of Air- and Freeze-Drying Methods on Total Phenolic Content and Antioxidant Activity of Fistulina antarctica and Ramaria patagonica Fructification - Gonzalez, Gabriela Celeste (2023)
Fistulina antarctica and Ramaria patagonica are wild edible fungi from Patagonia, which produce mushrooms that have been consumed since ancient times by those in local communities. Both species possess high protein and low fat contents and other bioactive compounds with remarkable antioxidant activity. Drying is a widely and commonly practiced preservation technique that is cost-effective. However, the process of drying can have an impact on the levels of bioactive compounds. In this study, the effects of drying methods on the total phenolic content (TPC) and antioxidant activity in the fructification of F. antarctica and R. patagonica were estimated. The analysis was conducted using fructifications that were fresh-frozen, dried at 50, 60, and 70 °C, and freeze-dried. The TPC was significantly higher for the fructifications that were fresh-frozen and dried at 60 °C in R. patagonica (with values of 14.78 and 13.67 mg GAE/mg of extract, respectively). Also, the fresh-freezing, freeze-drying. and 60 °C methods exhibited the highest inhibition of free radicals. In addition, R. patagonica had a notably higher concentration of phenols and showed higher antioxidant capacity than F. antarctica. The greatest losses concerning phenols occur in F. antarctica in the three evaluated air-drying temperatures (36.57, 29.76, 39.47% in 50, 60 and 70 °C respectively, compared with fresh-frozen). TPC and antioxidant activity were higher in fresh-frozen and freeze-dried samples. A drying temperature of 60 °C is advisable for both species, considering drying time and bioactivity. Overall, the fructifications from different processing methods exhibited unique functional properties. This information can be utilized to optimize the postharvest preservation and maximize the potential applications of these mushrooms.